1998 Reform Movement - H. Agus Rustamana; Putry Maharani Adillah; Zamin Zatua (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The 1998 reform movement was a social movement that was born from the demands of young intellectuals in the campus community. In historical records, the New Order student movement in Indonesia reached its peak in 1998, to demand reform of the New Order government with the removal of Soeharto from his position as president, and demands for improvements such as amendments to the 1945 Constitution, an end to the ongoing economic crisis, and other similar things. This movement carried out by students gained momentum when the monetary crisis occurred, prices of necessities soared, and people's purchasing power decreased. The demand to remove President Soeharto became a national agenda by the student movement who wanted reform and this of course received sympathy and support from the people. The aim of this research is to determine the occurrence of the 1998 reform movement and the role of pupils, students and society in facing the 1998 reform movement. The method used in this research uses a descriptive analysis method, namely research by collecting data according to the truth, then the data is compiled, processed and analyzed to be able to provide an overview of the existing problem, using several previous literature sources.